2018
DOI: 10.5897/ajbm2018.8587
|View full text |Cite
|
Sign up to set email alerts
|

Untangling the concept of entrepreneurship towards a common perspective

Abstract: There continues to be a lack of a commonly agreed perspective of entrepreneurship despite the concept being studied for a long period of time. Definitions of the concept and constructs of study in the field have depended on the researcher's conceptualisation of what constitutes entrepreneurship and as a result there are variations in the study focus and measurement of entrepreneurship. An analysis of literature was therefore conducted to untangle the concept of entrepreneurship towards a common perspective des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
(167 reference statements)
0
6
0
Order By: Relevance
“…A good way to start this section is by stating that entrepreneurship is not founded on a static profile of people and interests (Kerr et al, 2018; Mwatsika et al, 2018), but it is rather a term attributed to the set of actions that lead to the creation of new products and services, which can vary by, both, interests and opportunity evaluation marked at the individual (Kerr et al, 2018) and group level (Parker, 2018). The latter is an important factor, as literature shows certain differences in the set of business founded by groups, such as gender.…”
Section: Introductionmentioning
confidence: 99%
“…A good way to start this section is by stating that entrepreneurship is not founded on a static profile of people and interests (Kerr et al, 2018; Mwatsika et al, 2018), but it is rather a term attributed to the set of actions that lead to the creation of new products and services, which can vary by, both, interests and opportunity evaluation marked at the individual (Kerr et al, 2018) and group level (Parker, 2018). The latter is an important factor, as literature shows certain differences in the set of business founded by groups, such as gender.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that the researchers used different questions to measure these factors (Zarefard and Cho, 2018;Robledo et al, 2015;Maes et al, 2014;Fayolle & Liñán, 2014;Krueger et al, 2000;Ajzen, 1991;Mwatsika, 2015;Glanz et al, 2015;Fishbein & Ajzen, 2010;Sahinidis et al,2021). The final questions for attitudes and social norms were based on the following surveys: Sahinidis et al (2021), Mwatsika, (2015, Glanz et al (2015); Mwatsika et al(2018), Shapero (1984), Armitage and Conner (2001), Fishbein and Ajzen (2010), Madden et al(1992), Asimakopoulos et al (2019), andKrueger et al (2000). Table 1 below summarizes the items of the applied measures.…”
Section: Methodsmentioning
confidence: 99%
“…In order to ensure the validity of the research, the online questionnaire that was constructed was based on previous studies on EI (Ajzen, 2002;Ajzen, 1991;Glanz et al, 2015;Mwatsika et al, 2018;Mwatsika, 2015;Armitage & Conner, 2001;Madden et al, 1992;Shapero, 1984;Fishbein & Ajzen, 2010;Bandura, 1997;Krueger et al, 2000).…”
Section: Source: Authors' Own Workmentioning
confidence: 99%
“…There is no certainty that all the authors who research about this topic refer to the same thing (Mwatsika et al, 2018), since most of them visualize it as a methodology and not as a situation influenced by the environment (Acs et al, 2016). This is how entrepreneurship is directly related to the response to the environment in a creative and innovative way, and the actions that the entrepreneur commits to carry out at the moment of starting his company (Palanivelu & Manikandan, 2015;Rosero & Molina, 2008).…”
Section: Entrepreneurshipmentioning
confidence: 99%